SISTEM BOOKING PARKIR MALL DENGAN IDENTIFIKASI PLAT NOMOR KENDARAAN BERBASIS ANDROID - Muhammad Alvie Zaimuddin; Slamet Winardi; Sri Wiwoho Mudjanarko; Benediktus Anindito (Jurnal TAM (Technology Acceptance Model), 2019)
Many urban people spend time relieving fatigue due to the pressure of saturating work by walking in the mall or for mothers hunting for brand items that are being discounted at the mall, unfortunately when going to the mall it's hard to find a large enough parking lot. Look for a parking lot from the basement floor to the top floor and change from building one to another building to just get a parking space. Most malls do not provide information on the availability of parking spaces and the absence of officers directing to parking locations is still available. Some malls have provided information on the availability of parking spaces but have not yet provided which locations are still empty. From the description above we provide a solution to get a parking space when you want to visit the mall so that it can provide comfort when going to parking and time is not wasted to find parking locations. The parking booking system created will make it easy to get a parking space when going to the mall. With a vehicle number plate identification system and combined with an Android system, mall customers will easily get a parking space.